EPILEPSY AND PINEAL HORMONE: CURRENT STATE OF THE PROBLEM - O. M. Oleynikova; E. N. Kareva; M. A. Bogomazova; G. G. Avakyan; Yu. V. Lagutin; G. N. Avakyan (Эпилепсия и пароксизмальные состояния, 2016)
The pineal gland hormone melatonin is the main regulator of biological rhythms. It affects sleep, brain bioelectric activity and seizures. The majority of experimental and clinical studies are confirmed the anticonvulsant properties of melatonin. However, in the scientific literature there is no data on the concentration of melatonin in adult patients with epilepsy and epileptic syndromes. Thus study of melatonin in adult patients was developed. The evening (1 hour before bedtime), night concentrations (morning), and excretion of melatonin in 54 patients with focal symptomatic epilepsy at the age of 21 to 47 years were evaluated. It was found that seizures provoke a decrease of melatonin concentration.